A Statewide Collaboration to Deliver and Evaluate a Pediatric Critical Care Simulation Curriculum for Emergency Medical Services - Farrell, Caitlin; Dorney, Kate; Mathews, Bonnie; Boyle, Tehnaz; Kitchen, Anthony; Doyle, Jeff; Monuteaux, Michael C.; Li, Joyce; Walsh, Barbara; Nagler, Joshua; Chung, Sarita (Frontiers in Pediatrics, 2022)
Objective Care of the critically ill child is a rare but stressful event for emergency medical services (EMS). Simulation training can improve resuscitation care and prehospital outcomes but limited access to experts, simulation equipment, and cost have limited adoption by EMS systems. Our objective was to form a statewide collaboration to develop, deliver, and evaluate a pediatric critical care simulation curriculum for EMS providers. Methods We describe a statewide collaboration between five academic centers to develop a simulation curriculum and deliver it to EMS providers. Cases were developed by collaborating faculty, reviewed by EMS directors, and based on previously published curricula and needs assessment. Three scenarios requiring recognition and management of critically ill infants and children were included. The curriculum was delivered 5 times over 6 months. We evaluated curriculum effectiveness with a prospective, interventional, single-arm educational study using pre-post assessment design to assess the impact on EMS provider knowledge and confidence. To assess the intervention effect on knowledge scores while accounting for nested data, we estimated a mixed effects generalized regression model with random effects for region and participant. We assessed for knowledge retention and self-reported practice change at 6 months. Qualitative analysis of participants’ written responses following the curriculum and at 6 months was performed using the framework method. Results 78 emergency medical technicians (EMTs) and 109 paramedics participated in the curriculum. Most participants were male (69%) and paramedics (58%). One third had over 15 years of clinical experience. In the regression analysis, mean pediatric knowledge scores increased by 9.8% (95% CI: 7.2%, 12.4%). Most (93% [95% CI: 87.2%, 96.5%]) participants reported improved confidence caring for pediatric patients. Though follow-up responses were limited, participants who completed follow up surveys reported they had used skills acquired during the curriculum in clinical practice. Conclusion Through statewide collaboration, we delivered a pediatric critical care simulation curriculum for EMS providers that impacted participant knowledge and confidence caring for pediatric patients. Follow-up data suggest that knowledge and skills obtained as part of the curriculum were translated into practice. This strategy could be used in future efforts to integrate simulation into EMS practice.